GAMBARAN PENGETAHUAN TENTANG DISMENOREA (NYERI HAID) PADA SISWI SMK MUTIARA 17 AGUSTUS BEKASI BULAN JULI 2019 - Niko Prasetya; Mega Efrilia; Maria Margaretha Ika D.A (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2021)
In adolescent girls there is a physical change that is a change in the reproductive organs which is marked by the arrival of menstruation. Menstruation experienced by young women can cause problems, one of which is dysmenorrhoea. Almost all women experience discomfort during menstruation, such as discomfort in the lower abdomen and are usually accompanied by nausea, dizziness, even fainting. Most women experience dysmenorrhoea in varying degrees of severity. The occurrence of dysmenorrhoea in adolescents causes disturbed activity and concentration. Efforts to manage dysmenorrhoea during mestruation are by using anti-pain medications (analgesics), compressing with warm water and consuming fruits and vegetables. The purpose of this study is the author wants to know the description of knowledge about dysmenorrhoea (menstrual pain) which includes understanding, prevention, causes and treatment of dysmenorrhoea in SMK Mutiara 17 Agustus Bekasi students. This type of research is a type of non-experimental research with descriptive methods. The sampling technique used by the writer is Stratified Random Sampling and to calculate the determination of the number of samples carried out based on the Slovin formula. Where the population of Mutiara August 17 Bekasi Bekasi students numbered 177 students after being calculated using the Slovin formula, then a sample of 123 students was obtained which would be divided into 36 class X students, 41 class XI students, and 46 class XII students. The data needed in this study is the data used through the results of distributing questionnaires to respondents. The results showed that of the 123 respondents, 112 students (91%) had good knowledge of dysmenorrhoea, 9 students (7%) had sufficient knowledge about dysmenorrhoea, and 2 students (2%) lacked knowledge of dysmenorrhoea.